Anti- DPPX Antibody Encephalitis With a Pan-Positive Review of Systems. (5th December 2022) - Donmez, Mustafa; Mazzola, Maria; Deeb, Wissam; Ionete, Carolina
Abstract : Objective: NA. Background: Subacute encephalitides like anti-DDPX encephalitis are challenging diagnoses due to their unusual presentations. Anti-DPPX encephalitis usually involves gastrointestinal, nervous, and respiratory systems. Common symptoms include diarrhea, weight loss, cognitive dysfunction, amnesia, myoclonus, tremor, and exaggerated startle response. Design/Methods: NA. Results: A 48-year-old man with no significant past medical history was referred to the neurology clinic to evaluate his tremor. The patient's first symptoms included alternating diarrhea and constipation, weight loss, fatigue, generalized pain, chest pain, dyspnea, and leg cramps. Several emergency departments, primary care physicians, and specialty clinic visits did not yield a diagnosis. During the first neurology clinic visit, he reported new urinary symptoms, chills, insomnia, tremor, anxiety, and depression. His physical exam revealed exaggerated physiological tremor only. During the second neurology clinic visit and resultant urgent admission, he reported new symptoms of forgetfulness, inattention, muscle jerks, numbness in the extremities, and seizure-like episodes. His exam was remarkable for mild left-sided rigidity and MOCA of 23/30 with impairment in delayed recall. The patient's MRI brain with and without contrast and spot EEG were unremarkable. CSF studies were negative except for protein elevation with lymphocytic pleocytosis. The patient's autoimmune CSF panel was positive for anti-DPPX antibodies, though available only after discharge. The patient was urgently seen in the neuroimmunology clinic and received a steroid course and monthly rituximab. The patient is improved with the treatments. His repeat MOCA 28/30 and returned to working full-time. Conclusions: Anti-DPPX antibody encephalitis has been reported in a handful of cases in the literature. It has a subacute presentation with often a delay to diagnosis–an average diagnosis time of 8 months after the onset of symptoms. We present the case to raise awareness about anti-DPPX encephalitis, especially its typical clinical triad of GI dysmotility, cognitive decline, and myoclonus/tremor.